Distribution and bioaccumulation of heavy metals in marine organisms in east and west Guangdong coastal regions, South China. Issue 2 (30th December 2015) - Zhang, Ling; Shi, Zhen; Jiang, Zhijian; Zhang, Jingping; Wang, Fei; Huang, Xiaoping
Abstract: Heavy metal (Cu, Pb, Zn, Cr, Cd, As) concentrations, distribution and bioaccumulation were studied in marine organisms in Guangdong coastal regions. Heavy metal concentrations and distribution in organisms showed characteristics according to areas and species. Heavy metal concentrations in most organisms were higher in west than in east, tightly related to the local industry structure and the disequilibrium of metal discharge. Generally, high heavy metal concentrations were detected in molluscs and low concentrations were detected in fish. Bioaccumulation factor was used to assess the accumulation level of marine organisms to heavy metals, of which Cd, Cu and As were the most accumulated elements. Accumulation abilities to heavy metals varied among organism species, such as Distorsio reticulate accumulating Cu, Zn, Cd, As, Loligo beka Sasaki accumulating Pb, Cu, Cr, and Turritella bacillum Kiener accumulating Zn, Cd, As. By comparison, Johnius belengeri, Argyrosomus argentatus, Cynoglossus sinicus Wu had relatively low accumulation abilities. Highlights: Heavy metal concentrations in marine organisms varied according to areas. Heavy metal distribution displayed significant variations based on organism species. Accumulation abilities to heavy metals varied according to organism species. Cd, Cu and As were the most accumulated heavy metals in marine organisms.